The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1093/ckj/sfw136
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seasonality on the dynamics of native Vitamin D repletion in long-term renal transplant patients

Abstract: Background: Renal transplant recipients (RTRs) are often Vitamin D (VitD) depleted as a result of both chronic kidney disease and mandated sun avoidance behaviours. Repleting VitD may be warranted, but how, and for how long, is unknown, as is the impact of seasonality on the success of repletion. We investigated the impact of seasonality on VitD status following VitD repletion in a large cohort of stable, long-term RTRs. Methods: Serum 25-hydroxyvitamin D [25(OH)D] concentrations and bone biochemistry paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The optimization of supplementation however should be guided by serum 25(OH) D and other calcemic parameters because vitamin D excess may lead to hypercalcemia, hyperphosphatemia and hypercalciuria, all of which has inverse relationship with graft function [ 15 ]. A recent study in UK has concluded vitamin D repletion (using a 6 month bolus intermediate dose schedule) to be safe and effective in stable RTRs, however the post-repletion fall in vitamin D status in the absence of maintenance supplementation was intriguing [ 32 ]. Further interventional studies are warranted to explore the implications of low vitamin D status in Nepalese RTR population and whether supplementation is really beneficial and is able to sustain the vitamin D status when coupled with sensible sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The optimization of supplementation however should be guided by serum 25(OH) D and other calcemic parameters because vitamin D excess may lead to hypercalcemia, hyperphosphatemia and hypercalciuria, all of which has inverse relationship with graft function [ 15 ]. A recent study in UK has concluded vitamin D repletion (using a 6 month bolus intermediate dose schedule) to be safe and effective in stable RTRs, however the post-repletion fall in vitamin D status in the absence of maintenance supplementation was intriguing [ 32 ]. Further interventional studies are warranted to explore the implications of low vitamin D status in Nepalese RTR population and whether supplementation is really beneficial and is able to sustain the vitamin D status when coupled with sensible sun exposure.…”
Section: Discussionmentioning
confidence: 99%